Content Analysis of Bahasa Melayu Skills in the Malaysian Preschool Curriculum - Habibah @ Artini Ramlie; Norshahrul Marzuki Mohd Nor; Wan Muna Ruzanna Wan Mohammad; Saifulazry Mokhtar (2020)
This study aimed to explore contents of Bahasa Melayu skills in the Malaysian preschool curriculum in Speaking and Listening Skill, Reading Skill and Writing Skill. Information obtained through the content analysis method. The National Preschool Curriculum 2001 and the National Preschool Standard Curriculum (Curriculumand Assessment Standard Document (KSPK DSKP 2017 Revision)) for Bahasa Melayu were used to identify the contents of the Bahasa Melayu skills in the preschool curriculum. The results showed that both documents fulfilled the needs of preschool education curriculum, which aimed for students to master language skills effectively. This paper also proposes teachers to prepare effective and fun instructional lessons for their students, which increases teacher’s creativity in designing teaching aids and varying their learning strategies according to the suitability of the students based on the latest KSPK 2017 Revision.